USULAN STRATEGI PERUSAHAAN MANUFAKTUR SEPEDA MELALUI IMPLEMENTASI QUANTITATIVE STRATEGIC PLANNING MATRIX - Ronald Sukwadi; Arinta Novitasari; Maria Magdalena Wahyuni Inderawati; Po Tsang B. Huang (Proceeding Maritime Business Management Conference, 2022)
Brand competition in the children's bicycle industry at this time is increasingly fierce. PT X Manufacturing (PT X), which produces tricycles for children, has experienced a decline in sales and has not reached its sales target for the past three years. This study proposes strategies regarding brand awareness, perceivedquality, and internal and the company's external environment. These can be the company's strengths, weaknesses, opportunities, and threats. The hybrid method used in this study consists of the EFE matrix, IFE matrix, IE matrix, SWOT matrix, and QSPM. Data collection techniques used interviews, observations,and questionnaires. The results showed that PT X was located in the V-quadrant in the IE matrix. A suitable strategy was a hold and maintain strategy consisting of market penetration and product development strategies. Seven alternative strategies were formed through the SWOT matrix, and priority strategies weredetermined using the QSPM method. The priority strategy was utilizing online media to increase marketing and public awareness of product brands. This strategy was chosen as a priority because it has the highest value of 5.936.